Początki łacińskiego tekstu pisma świętego = The origins of the Latin text of Holy Scripture - Królikowski, Janusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The history of the biblical text constitutes one of the significant threads in the history of humanity and especially in the history of the West. The Latin version of the biblical text has been particularly inscribed in history.
Keywords: Pismo Święte; język łaciński; język grecki; kultura starożytna; literatura łacińska; Holy Scripture; Latin; Greek; ancient culture; Latin literature